Evolution of drug resistance in Mycobacterium tuberculosis: a review on the molecular determinants of resistance and implications for personalized care - Dookie, Navisha; Rambaran, Santhuri; Padayatchi, Nesri; Mahomed, Sharana; Naidoo, Kogieleum (Journal of antimicrobial chemotherapy, 2018)
Drug-resistant TB (DR-TB) remains a significant challenge in TB treatment and control programmes worldwide. Advances in sequencing technology have significantly increased our understanding of the mechanisms of resistance to anti-TB drugs. This review provides an update on advances in our understanding of drug resistance mechanisms to new, existing drugs and repurposed agents. Recent advances in WGS technology hold promise as a tool for rapid diagnosis and clinical management of TB. Although the standard approach to WGS of Mycobacterium tuberculosis is slow due to the requirement for organism culture, recent attempts to sequence directly from clinical specimens have improved the potential to diagnose and detect resistance within days. The introduction of new databases may be helpful, such as the Relational Sequencing TB Data Platform, which contains a collection of whole-genome sequences highlighting key drug resistance mutations and clinical outcomes. Taken together, these advances will help devise better molecular diagnostics for more effective DR-TB management enabling personalized treatment, and will facilitate the development of new drugs aimed at improving outcomes of patients with this disease.